2006
DOI: 10.1002/cjg2.967
|View full text |Cite
|
Sign up to set email alerts
|

NMR Logging Porosity Activation and Data Processing Method

Abstract: Nuclear Magnetic Resonance (NMR) logging has been widely used in determining porosity of formation. However, it is found that porosity difference between NMR and conventional porosity logging is unacceptable in some oilfields in China. In this paper, we study the Magnetic Resonance Imaging Logging (MRIL) porosity acquisition activation and data processing method. The cause for porosity difference between MRIL and conventional porosity logging is analysed. It is found that there are rich smectite, illite and I/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) has been widely used as an effective tool for determining flow characteristic in porous media (Guan et al, 2002;Chen et al, 2006;Xiao and Xiao, 2008;Xie et al, 2006). The inverse relationship between the size of pore and relaxation rate of hydrogen forms the theoretical basis for studying the rock pore structure by T 2 spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) has been widely used as an effective tool for determining flow characteristic in porous media (Guan et al, 2002;Chen et al, 2006;Xiao and Xiao, 2008;Xie et al, 2006). The inverse relationship between the size of pore and relaxation rate of hydrogen forms the theoretical basis for studying the rock pore structure by T 2 spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation times of water in pore of different sizes are different. The clay-bound water, capillary-bound water, and movable water can be obtained by analyzing NMR log data [4,10] .…”
Section: Water Only In Poresmentioning
confidence: 99%
“…NMR logging gives quite accurate porosity in marine deposit or well sorted terrestrial sedimentation with little clay content 1) [1][2][3][4] . However, there exists significant differences between NMR and conventional log porosities in light hydrocarbon and /or heavy oil reservoir [5,6] .…”
mentioning
confidence: 99%
“…NMR logging can provide much information on porosity, capillary bound water, clay bound water, the volume of movable fluid, permeability, and pore size distribution (Coates et al, 1999;Dunn et al, 2002;Xie et al, 2006;Xie et al, 2008;Lu et al, 2007;He et al, 2005), all of which are important in well-logging for evaluating reservoirs, estimating water saturation, and understanding the fluid flow in pore networks, especially for prospecting and developing areas with a complex lithology. Akkurt and Prammer showed that NMR logging not only could provide porosity, bulk volume irreducible water, free fluids, permeability but also allow the identification and quantification of fluids in a reservoir.…”
Section: Introductionmentioning
confidence: 98%